2011
DOI: 10.1002/cncr.26315
|View full text |Cite
|
Sign up to set email alerts
|

Rates and predictors of colorectal cancer screening by race among motivated men participating in a prostate cancer risk assessment program

Abstract: Background Screening by fecal occult blood test and lower endoscopy have lowered colorectal cancer (CRC) mortality, but compliance gaps persist. Of concern are possible disparities in uptake of CRC screening between White and African American (AA) men. Our goal was to assess for disparities in uptake of CRC screening among men participating in a high-risk prostate cancer clinic. If present, such disparities could support hypotheses for further research examining racial differences in awareness and patient pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…One plausible explanation for lower follow‐through among NHB men is differential access to health care services among men aged <65 years—before Medicare eligibility. African Americans have lower use of cancer screening services and higher tumor stage at presentation for multiple cancer sites, including prostate . It has been demonstrated that poor health care access contributes to a delay in diagnosis and higher stage at diagnosis; and modifiable risk factors, such as screening practices and sociodemographic factors, may account for as much as 60% of racial differences in PCa stage at diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…One plausible explanation for lower follow‐through among NHB men is differential access to health care services among men aged <65 years—before Medicare eligibility. African Americans have lower use of cancer screening services and higher tumor stage at presentation for multiple cancer sites, including prostate . It has been demonstrated that poor health care access contributes to a delay in diagnosis and higher stage at diagnosis; and modifiable risk factors, such as screening practices and sociodemographic factors, may account for as much as 60% of racial differences in PCa stage at diagnosis .…”
Section: Discussionmentioning
confidence: 99%
“…Poisson regression was used to compare adjusted incidence rates (aIRR) between recipients and candidates and to test for interaction by racial/ethnic group. racial/ethnic differences in baseline risk are varied and are posited to include differences in exposures, diet, health conditions, lifestyle, genetics and screening rates (15)(16)(17)(18)(19)(20)(21)(22). In addition, cancer risk factors might have different effects across groups.…”
Section: Discussionmentioning
confidence: 99%
“…Hispanics have increased risk for cancers of the cervix, liver, gall bladder and stomach, and for acute lymphocytic leukemia, and decreased risk for cancers of the lung, colorectum, prostate and breast compared to whites (14). Many factors contribute to these differences, including differing environmental exposures, diets, occupations, health behaviors, genetics, socioeconomic status, access to health care and cancer screening behaviors (15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…First, because our study population is predominantly white and well-educated, our results may not be generalizable to minority populations or those with less education. Several studies have demonstrated differences in compliance with follow-up screening and procedures among people of different ethnic and racial backgrounds (54, 55). Therefore, the association between colonoscopy and advanced adenomas may be attenuated in groups who have lower compliance with recommendations.…”
Section: Discussionmentioning
confidence: 99%